Enhancing Building Energy Efficiency Through IoT Integration - Dhanush M; Shivashankar Hiremath; Subramanya R. Prabhu B. (International Journal of Machine Systems and Manufacturing Technology, 2024)
Building management systems featuring Internet of Things (IoT) technology provide a revolutionary way of maximizing user comfort and improve the use of energy. This study presents a comprehensive analysis of various components within an IoT subsystem utilized in building management, including Smart IoT Gateways, temperature and humidity sensors, lightweight database systems such as Tiny DB, and cloud communication platforms like Twilio. Each component plays a vital role in facilitating real- time monitoring, control, and data analysis, ultimately leading to informed decision-making and improved operational efficiency. A detailed examination of recent studies highlights the impact of daylight supplementation on user experience in office environments, showcasing positive user feedback regarding the integration of horizontal light pipes (HLP). Furthermore, the implementation of static pressure management in HVAC systems demonstrates significant potential for energy savings, with reductions exceeding 50% in certain scenarios. The study also addresses critical methodologies for ductwork calculations, emphasizing the Minimal Energy Dissipation Principle (Min EDP) as a robust alternative for analyzing airflow in duct networks. Additionally, various control techniques for air handling units (AHUs) are classified, ranging from classical methods to advanced strategies, underscoring the need for flexible and adaptive control mechanisms in HVAC systems. The findings underscore the importance of a well-implemented IoT framework, which not only enhances energy efficiency but also prioritizes user satisfaction and comfort in modern building environments. By synthesizing insights from various studies and practical applications, this research contributes to the ongoing discourse on sustainable building practices and the effective integration of IoT technologies in the quest for energy-efficient solutions.
Keywords: HVAC systems; IOT; Tiny DB; Twilio; energy efficiency; smart IoT gateway